A review of municipal solid waste management in the BRIC and high-income countries: A thematic framework for low-income countries. (January 2020) - Iyamu, H.O.; Anda, M.; Ho, G.
Abstract: Municipal Solid Waste Management (MSWM) is a challenging issue for low-income countries, impacting on the environment, socio-economic, health, aesthetics and infrastructure, due to the generated volume of wastes, treatment and disposal methods. This challenge is often impacted by the transitioning of MSWM from mostly unsustainable methods to a sustainable level. A meaningful MSWM transition requires an understanding and consideration of historical developments and common themes. This paper reviews the common themes limiting MSWM sustainability in the BRIC (Brazil, Russia, India and China) countries as well as the historical transition of MSWM to a sustainable level in some high-income countries (United States, Japan, Denmark, and Australia). The study focuses on the interaction of MSWM with technology systems, related environmental issues, socio-economic factors, influence on policy and decision making. The objective of the paper is to develop a holistic MSWM framework to address the prevailing issues, by systematic analysis of related and relevant literatures. The key MSWM findings drawn from the BRIC countries in this study is used to develop a thematic framework, underpinned by the different interacting factors of policy; environmental; socio-economic; and technology (PEST). The PEST thematic framework presents an adaptable systematic tool to policy and decision makers towards improving MSWM in low-income countries. Highlights: Technology approach, deemed suitable for the environment, advances sustainable MSWM. Systematic analysis of relevant literatures provides insight to MSWM issues. Awareness of historical transition of MSWM impacts future policies and developments. Thematic framework, adapted for low-income countries, fosters sustainable MSWM. The thematic framework promotes strategies and innovations for better MSWM.